Risk Factors Associated with Scabies Occurring in Islamic Boarding Schools: Literature Review - Aziz Setiawan; Qomaruddin, Mochammad Bagus; Sulistyowati, Muji (Universitas Airlangga, 2024)
Background: Islamic boarding schools in Indonesia, in particular, have classic health problems. Some diseases that are common in Islamic boarding schools are scabies, shortness of breath, fever, fainting, cough and cold with influenza, gastritis/ulcer, and so on. And the most common health problem in Islamic boarding schools is scabies. It seems that students who live in boarding schools are